2006
DOI: 10.1128/jvi.00241-06
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus Exerts Oncolysis by both Intrinsic and Extrinsic Caspase-Dependent Pathways of Cell Death

Abstract: Newcastle disease virus (NDV), an avian paramyxovirus, is tumor selective and intrinsically oncolytic. Here, we present evidence that genetically modified, recombinant NDV strains are cytotoxic to human tumor cell lines of ecto-, endo-, and mesodermal origin. We show that cytotoxicity against tumor cells is due to multiple caspase-dependent pathways of apoptosis independent of interferon signaling competence. The signaling pathways of NDV-induced, cancer cell-selective apoptosis are not well understood. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
205
4
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(218 citation statements)
references
References 62 publications
(76 reference statements)
6
205
4
3
Order By: Relevance
“…Virus infection has been observed to be associated with apoptosis [8][9][10][11], and the molecular mechanisms and signal pathways have been disclosed in virus infection of mammal cells [12,13]. Apoptosis of fish cells can be also triggered by virus infection [14][15][16], but systematic studies on mitochondrial dynamics and the molecular mechanisms are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Virus infection has been observed to be associated with apoptosis [8][9][10][11], and the molecular mechanisms and signal pathways have been disclosed in virus infection of mammal cells [12,13]. Apoptosis of fish cells can be also triggered by virus infection [14][15][16], but systematic studies on mitochondrial dynamics and the molecular mechanisms are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic activity of another NDV lentogenic strain (rLaSota) in a variety of tumor cells was demonstrated previously but no comparison to nontumorigenic cells was shown. 3 Interestingly, when the apoptotic activities of NDV and ETO, a standard anti cancer drug, were compared, the two agents appear to function in a different mode. Although proliferating nontumorigenic cells were highly sensitive to ETO, as compared to tumor cells, they were less sensitive to NDV.…”
Section: Discussionmentioning
confidence: 99%
“…Newcastle disease virus (NDV), an avian paramyxovirus, has been evaluated in experimental models and in some clinical studies as an anti cancer agent and some therapeutic benefits have been reported. [3][4][5] Two major approaches were undertaken in these studies: first, the virus was applied to directly infect and kill the tumor cells. 4,[6][7][8] Second, the virus was used as an immunomodulatory agent by infecting autologous cells ex vivo, followed by injection of the 'xenogenized' cells to induce immune surveillance against the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Single cell suspensions were obtained from spleens and lymph nodes of Balb/c mice. Lysis of erythrocytes was performed with 155 mM NH 4 Cl, 10 mM KHCO 3 and 0.1 mM EDTA. Mouse T cells were purified using the Dynal mouse T cell Negative Isolation Kit from Invitrogen (Karlsruhe, Germany).…”
Section: Methodsmentioning
confidence: 99%